Simultaneous Probe of the Charm and Bottom Quark Yukawa Couplings Using tt[over ¯]H Events. - Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Andrejkovic,JW; Benato,L; Bergauer,T; Dragicevic,M; Giordano,C; Hussain,PS; Jeitler,M; Krammer,N; et al. (Phys Rev Lett, 2026)
A search for the standard model Higgs boson decaying to a charm quark-antiquark pair, H→cc[over ¯], produced in association with a top quark-antiquark pair (tt[over ¯]H) is presented. The search is performed with data from proton-proton collisions at sqrt[s]=13  TeV, corresponding to an integrated luminosity of 138  fb^{-1}. Advanced machine learning techniques are employed for jet flavor identification and event classification. The Higgs boson decay to a bottom quark-antiquark pair is measured simultaneously and the observed tt[over ¯]H(H→bb[over ¯]) event rate relative to the standard model expectation is 0.91_{-0.22}^{+0.26}. The observed (expected) upper limit on the product of production cross section and branching fraction σ(tt[over ¯]H)B(H→cc[over ¯]) is 0.11 (0.13) pb at 95% confidence level, corresponding to 7.8 (8.7) times the standard model prediction. When combined with the previous search for H→cc[over ¯] via associated production with a W or Z boson, the observed (expected) 95% confidence interval on the Higgs-charm Yukawa coupling modifier, κ_{c}, is |κ_{c}|<3.5 (2.7), the most stringent constraint to date.